Predictors of Healthy Nutrition Behaviors among Elderlies of Kalat County based on Health Belief Model - Mohammad Ali Morowatisharifabad; Fatemeh Amani; Fatemeh Kaseb; Seyedeh Mahdieh Namayandeh (Elderly Health Journal, 2018)
Introduction: Rapid changes in lifestyle, especially in nutritional aspects of the elderly, have led to many chronic diseases. Therefore, attention to nutritional needs of the elderly is an essential issue. The purpose of this study was to determine the predictors of healthy nutrition behaviors based on health belief model (HBM) in the elderlies of Kalat city, Razavi Khorasan Province, Iran.. Methods: The cross-sectional study was carried out on 200 elderlies aged 60 years and older who were covered by comprehensive health services centers in the city of Kalat. The participants were selected by multistage random sampling. The data collection tools included a researcher-made questionnaire for measuring HBM constructs regarding healthy nutrition and also a Food Frequency Questionnaire for measuring Healthy nutrition behaviors. Data were analyzed by SPSS software using descriptive statistics, t-test, one-way ANOVA, Pearson correlation coefficient and linear regression. Results: The mean score of nutritional knowledge of the elderlies was 7.75 ± 2.14 (possible score 0-15) and the mean score of healthy nutrition behaviors was 1.62 ± 1. 23 (possible score 0-5). Healthy nutrition behaviors were significantly correlated with perceived benefits (r = 0.254), self-efficacy (r = 0.244) and cues to action (r = 0.334) (p < 0.05). Linear regression showed that cues to action (β = 0.353), perceived benefits (β = 0.199) and self-efficacy (β = 0.181) were significant predictors of healthy nutrition behaviors. Conclusion: The level of healthy nutrition behaviors in the elderlies is not desirable, and cues to action, perceived benefits and self-efficacy are the most important predictors of these behaviors. Paying attention to these factors helps educators and other health professionals in designing appropriate intervention programs.